Problem-Solving-Based E-LKPD as an Innovation in Science Education to Improve Problem-Solving Skills and Science Literacy: A Systematic Literature Review - Rosyida Adinia; Sigit Saptono; Dyah Rini Indriyanti; Novi Ratna Dewi (Journal of Educational Sciences, 2026)
The low levels of problem-solving skills and science literacy among students in Indonesia call for a learning approach that cultivates critical thinking skills and the application of scientific information to solve real-world problems. This study aims to analyze the trends and impacts of implementing Problem Solving-based E-LKPD media in science learning through the Systematic Literature Review (SLR) method. The article search was conducted systematically following PRISMA standards by analyzing various research articles published between 2016 and 2026 via the Google Scholar database. The analysis results indicate that integrating the Problem Solving model into digital media such as E-LKPDs can provide students with a more interactive and contextual learning experience. In conclusion, the use of Problem Solving-based E-LKPDs has proven to be significantly more effective in enhancing problem-solving skills and science literacy compared to conventional methods. As a follow-up, the researchers suggest developing instructional media with more explicit and structured syntax. Additionally, further testing through quasi-experimental methods is needed to obtain more comprehensive and valid results regarding the improvement of these two competency aspects across various educational levels.